Synthesis and characterization of novel Mannich's bases incorporated with Ibuprofen an Biginelli Derivatives - Layth W. Abdullah; Hanaa K.Saleh; Mustafa R. Aeyyd (Tikrit Journal of Pure Science, 2023)
In this work, a series of novel Mannich's bases incorporated with Ibuprofen core and Biginelli derivatives have been reported. The synthesis process was dependent on linking Ibuprofen hydrazone with Isatin to Biginelli derivatives via methylene group of formaldehyde. The new compounds have been characterized using FT-IR spectroscopy, 1H-NMR spectroscopy and the physical properties.